Drug resistance of Mycobacterium tuberculosis strains in southern Brazil - Laynara Katize Grutzmacher; Eduardo Monguilhott Dalmarco; Solange Lucia Blatt; Caio Mauricio Mendes de Cordova (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: The aim of this work was to evaluate the prevalence of Mycobacterium tuberculosis (MT) strains with mutations that could result in resistance to the main drugs used in treatment in a region with one of the highest numbers of tuberculosis (TB) cases in southern Brazil. METHODS: Deoxyribonucleic acid (DNA) from 120 sputum samples from different patients suspicious of pulmonary tuberculosis who attended the Municipal Public Laboratory for Mycobacterium sp. diagnosis was directly amplified and analyzed by PCR-SSCP. The DNA was amplified in known hotspot mutation regions of the genes rpoB, ahpC, embB, katG, inhA, and pncA. RESULTS: The percentage of samples positive by culture was 9.2% (11/120); 5% (6/120) were positive by bacilloscopy and MT-PCR, and DNA fragments of the aforementioned resistance genes could be amplified from seven (7) of the eleven (11) samples with positive results, either by culture or PCR/bacilloscopy. All presented a SSCP pattern similar to a native, nonresistant genotype, with the ATCC strain 25177 as control, except for one sample (0.01%), which presented a SSCP profile demonstrating mutation at the embB gene. CONCLUSIONS: These results are consistent with the empirical observations by physicians treating TB patients in our region of a low occurrence of cases that are refractory to conventional treatment schemes, in contrast to other parts of the country. Continued surveillance, especially molecular, is essential to detect and monitor the outbreak of MT-resistant strains.